THE ACQUISITION OF ENGLISH AS A FOREIGN LANGUAGE IN PARE EAST JAVA (KAMPUNG INGGRIS) (A Case Study Of What And How The Acquisition Of English In Pare) - Nurhayati Nurhayati; Nurmala Hendrawaty; Tri Angkarini (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2013)
The purposes of the research are to investigate and find out how English community in Pare Kediri is built, what the techniques used to make the community speak English without any reluctance, and how the community in Pare Kediri acquires English. The research was conducted from January 22nd to 25th 2013 in Pare Kediri, East Java which is famous as “Kampung Inggris”. There are approximately134 English courses in Pare sub district, this research focused on observing and distributing questionnaire in Pelem village. This study employed a case study method, and the data were collected by ways of observations, questionnaires, and interviews. Based on the research findings, English community in Pare Kediri is built because there are more than 100 English courses in that sub district only. In addition, mostly English courses implement some techniques as drilling, singing, debating, and playing games and also outing class as one of their learning programs. These teaching techniques make learners are active and creative. Finally, the community in Pare Kediri acquires English by using it as their daily communication and having discipline and commitment to obey the rules implemented by English courses there.Key words: Language Acquisition, English Community, and Speaking.